2017
DOI: 10.1021/acs.inorgchem.7b01516
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Performances of Nondoped OLEDs Using Carbazole and Diphenylphosphoryl-Functionalized Ir(III) Complexes as Active Components

Abstract: Nondoped electroluminescent devices offer advantages over their doped counterparts such as good reproducibility, reduced phase separation between host and guest materials, and potential of lower-cost devices. However, low luminance efficiencies and significant roll-off values are longstanding issues for nondoped devices, and a rational design strategy for the preparation of efficient phosphors is highly desired. In this work, cyclometalated Ir(III) complexes 3CzIr(mtpy), 4CzIr(mtpy), 3POIr(mtpy), and 4POIr(mtp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…The HOMO energy levels determined from the oxidation potentials are in good agreement with those obtained from DFT calculations. Similarly, the LUMO energy levels determined from the onsets of the emission spectra, in MeTHF, at room temperature show the same trend as those obtained from DFT calculations.…”
Section: Resultssupporting
confidence: 59%
“…The HOMO energy levels determined from the oxidation potentials are in good agreement with those obtained from DFT calculations. Similarly, the LUMO energy levels determined from the onsets of the emission spectra, in MeTHF, at room temperature show the same trend as those obtained from DFT calculations.…”
Section: Resultssupporting
confidence: 59%
“…These characteristics spark research interest in exploring potential binding geometries with novel ancillary ligands. After the seminal work by Watts et al on triply ortho-metalated Ir­(III) complexes in the 1980s, diverse mono-, bis-, and triscyclometalated complexes with different polypyridine ligands or cyclometalating ligands have been reported. , Among these complexes, biscyclometalated monocationic Ir­(III) complexes are discovered to play a crucial role in various applications, such as sensitized photo-upconversion, organic light emitting diodes (OLEDs), light-emitting electrochemical cells (LEECs), , photodynamic therapy, nonlinear optics, photocatalysis, and bioimaging and biosensing …”
Section: Introductionmentioning
confidence: 99%
“…The details of the synthetic conditions of BPhCz-pimi and BPhCz-mimi referred to the previous studies and can be found in the experimental section. [20][21][22] BCzPh-pimi and BCzPh-mimi can be readily dissolved in dichloromethane, chloroform, and toluene. Consequently, they were purified by column chromatography and identified by 1 H NMR spectroscopy, 13 C NMR spectroscopy, and high-resolution mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%